Implementation of Project-based Learning Model to Increase Creativity of Fifth Grade Students at 1st Ledok Salatiga Elementary School - Luth Prasandi Eko Wibowo; Adi Winanto (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2023)
Creativity is needed to face challenges in the digital era and industrial revolution 4.0. This research aims to increase the creativity of students through the Project-based Learning (PjBL) model. The type of research is classroom action research. This study consisted of pre-cycle and two cycles. Each cycle carried out the stages of action planning, action implementation, observation, and reflection. The subjects of this study were 21 students in fifth grade at  1st Ledok Salatiga Elementary School. Instruments used in data collection by observation sheets and creativity tests. Data analysis uses an interactive model consisting of data condensation, data presentation, and drawing conclusions. The indicator of this research is an increase in the average value of creativity of at least 85%. The results showed that the acquisition of a creativity score in pre-cycle was 41% (low category), creativity in cycle I obtained 61.5% (moderate category) and in cycle II increased creativity obtained 85% (high category). It can be concluded that the implementation of the PjBL model can increase the creativity of fifth grade students at 1st Ledok Salatiga Elementary School.